PENGARUH LIKUIDITAS, LEVERAGE, DAN PROFITABLITAS TERHADAP KESULITAN KEUANGAN DI BURSA EFEK INDONESIA - Fredy, Hans; Trisnawati, Estralita (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
The purpose of this study is to obtain empirical evidence of the effect of liquidity, leverage, and profitability on financial distress in bank companies listed on the Indonesia Stock Exchange during 2019-2021. This research was conducted using a sample of 28 bank companies with the sample selection method used was purposive sampling. The results show that liquidity has a significant positive effect on financial distress, leverage has effect but no significant on financial distress, and profitability has no significant negative effect on financial distress.